Prognostic Impact of Phenotypic and Genetic Features of Pancreatic Malignancies - Mikhail B. Potievskiy; Lidia A. Nekrasova; Ivan V. Korobov; Ekaterina A. Bykova; Ruslan I. Moshurov; Pavel V. Sokolov; Peter A. Shatalov; Natalia A. Falaleeva; Leonid O. Petrov; Vladimir S. Trifanov; Sergey A. Ivanov; Peter V. Shegai; et al. (Life)
Pancreatic cancer is a tumor with a poor prognosis, and improving its survival outcomes remains a formidable challenge, requiring a multidisciplinary approach that integrates innovative surgical and pharmacological strategies, guided by molecular and genetic insights. The pathomorphological and genetic characteristics of pancreatic cancer, reflected in morphological, immunohistochemical, and serological marker expression, reveal key patterns of tumor genotypic changes during carcinogenesis, aiding in prognostic evaluation and clinical strategy development. The mutational profile of pancreatic tumors is quite heterogeneous and diverse in terms of mutated genes, including in relation to morphological subtypes, but certain patterns have been identified as a result of studies. Pancreatic adenocarcinoma, for instance, is frequently driven by mutations regulating cell division (KRAS). The disease prognosis often depends on the morphological subtype and tumor microenvironment. Neuroendocrine tumors of the pancreas are characterized by a number of pathogenetic features that distinguish them from adenocarcinomas. Thus, neuroendocrine tumors are characterized by mutations of the MENIN protein, which prevents cells from entering the mitosis phase by stimulating the expression of cell cycle regulators. Thus, epithelial and neuroendocrine malignancies of the pancreas differ in immunohistochemical and genetic features, but there are similar mechanisms of pathogenesis, such as BRCA1 and BRCA2 gene mutations, impaired expression of p53 antioncogene, and HIF-2α and mTOR receptor mutations. The predictive impact of serological markers, such as CA 19-9 and CEA, offers insights into tumor metastasis and long-term outcomes, emphasizing the need for personalized therapeutic strategies. Tailoring treatments based on individual molecular profiles holds promise for improving prognosis, as the genetic landscape of pancreatic tumors varies significantly between patients. This underscores the importance of a systematic, patient-specific approach that addresses tumor heterogeneity, resistance mechanisms, and the molecular underpinnings of carcinogenesis.